2021
DOI: 10.14218/jcth.2020.00118
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis B Virus M204V Mutation Quantitatively via Real-time PCR

Abstract: Background and Aims: Drug-resistant DNA mutations of the hepatitis B virus (HBV) affect treatment response in chronic hepatitis B patients. We have established a new, sensitive, specific, accurate and convenient real-time PCR method to detect HBV mutations quantitatively. Methods: Blood samples were collected from patients showing viral breakthrough, primary nonresponse, or poor response during treatment, and mutations were detected via direct sequencing to assess our method. A plasmid containing the M204V mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The real-time PCR technique has also recently been applied to quantitatively detect hepatitis B virus (HBV) M204V mutation [ 29 ]. This is an amino acid substitution in the hepatitis B viral polymerase linked to viral resistance to nucleotide analogs, the main treatment option for patients suffering from chronic hepatitis B.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The real-time PCR technique has also recently been applied to quantitatively detect hepatitis B virus (HBV) M204V mutation [ 29 ]. This is an amino acid substitution in the hepatitis B viral polymerase linked to viral resistance to nucleotide analogs, the main treatment option for patients suffering from chronic hepatitis B.…”
Section: Applicationsmentioning
confidence: 99%
“…For quantitative measurement, a plasmid carrying the M204V mutation was synthesized. The method showed advantages in terms of sensitivity, specificity, and efficiency in detecting HBV M204V mutations and provided a new option for monitoring drug resistance [ 29 ]. A mismatch amplification mutation assay for rapid detection of Neisseria gonorrhoeae , the causative agent of the sexually transmitted infection gonorrhea, has been developed using a real-time PCR platform.…”
Section: Applicationsmentioning
confidence: 99%
“…According to the results, Liang et al 17 confirmed probes 204-2-VP2 and 204-2-IP2 with a positive rate of 100% and the false positive rate of 0%. Furthermore, the amplification curves showed a highly linear relationship between Ct values and the amount of serially diluted plasmid DNA for the primers and probes (R 2 =0.996, slope=−3.723), indicating an appropriate quantitative detection of M204V/I.…”
mentioning
confidence: 99%
“…To counter the disadvantages of the methods above, Liang et al 17 developed a real-time PCR assay aimed at monitoring the reaction process and quantitatively detecting HBV resistance mutations. Compared with the above-mentioned commonly used methods, this method has a streamlined operation process and can detect resistance mutations with a rate of less than 10%, whereas its disadvantage is that it can only detect known mutation sites by using designed probes and primers.…”
mentioning
confidence: 99%
See 1 more Smart Citation